TINJAUAN TINGKAT KESEGARAN JASMANI SISWA SMP NEGERI 1 SATU ATAP SUNGAI NIUR KECAMATAN MEMPURA KABUPATEN SIAK - Asriani, Nunik; Saripin, Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This problem in this research is during physical activity in the field most of the students are much less excited, lazing and someare choosing to sit than do the moving activity, then the students are many who complain of pain that is felt in the legs and abdomen, and many students are struggling while breathing after warming up such as running around the field. The purpose of this research to determine the level of physical fitness among all students schooled in SMP Negeri 1 One Roof Niur River Siak District of Mempura. This research is descriptive, as it aims to describe what happened. Based on the results of data processing that has been done it can be concluded that the level of Student Physical Fitness SMP Negeri 1 One Roof Niur River District of Mempura Siak by the number of samples studied as many as 23 students. Test instrument used for data collection Level Physical Fitness namely Tests Physical Freshness Indonesia (TKJI) consists of five measurements are Running 50 meters, Suspension Lift Body for Men and Hanging Elbow Bend For Women, Baring sitting, Skip Upright, Running 1000 meters for Men and Running the 800 meters for Women. Based on the results of research and data processing has been done it can be concluded that the level of Student Physical Fitness SMP Negeri 1 One Roof Niur Sungai Siak District of Mempura with a sample of 23 students with an average of 16.74, which means that the rate of Physical Fitness Junior High School Students 1 One roof Niur River District of Mempura Siak categorized Medium. Key Words: Level of Physical Fitness.